Cadmium-sensitive, cad1 mutants of Arabidopsis thaliana are phytochelatin deficient. - Howden, R (1995)
An allelic series of cad1, cadmium-sensitive mutants of Arabidopsis thaliana, was isolated. These mutants were sensitive to cadmium to different extents and were deficient in their ability to form cadmium-peptide complexes as detected by gel-filtration chromatography. Each mutant was deficient in its ability to accumulate phytochelatins (PCs) as detected by high-performance liquid chromatography and the amount of PCs accumulated by each mutant correlated with its degree of sensitivity to cadmium. The mutants had wild-type levels of glutathione, the substrate for PC biosynthesis, and in vitro assays demonstrated that each of the mutants was deficient in PC synthase activity. These results demonstrate conclusively the importance of PCs for cadmium tolerance in plants.